Infrared radiation transfer through semitransparent windows supporting absorbing droplets. (15th September 2022) - Simsek, Eylul; Williams, Megan J.; Hoeniges, Jack; Zhu, Keyong; Pilon, Laurent
Highlights: First infrared transmittance and reflectance data for droplet-covered glass windows. The droplet contact angle varied from 26 to 76o and surface area coverage up to 60%. In most cases, the droplets reduce the transmittance due to absorption and/or back-scattering. Measurements agree well with predictions from Monte Carlo ray-tracing simulations. Solar transmittance of water droplet-covered glass windows can decrease significantly. Abstract: Water droplets are commonly observed on the inner or outer surface of solar energy conversion systems due to rain or condensation. These droplets affect the systems' efficiency and thermal load. This study experimentally and numerically investigates infrared radiation transfer through semitransparent windows covered with droplets on their front or back sides. In order to validate our previously developed numerical code and to facilitate the systematic characterization of the samples, acrylic droplets (instead of water) were deposited onto glass windows with contact angle ranging from 26 to 76° and projected surface area coverage from 0% to 60%. The measured transmittance of glass windows with slightly absorbing droplets on the front increased while the reflectance decreased with increasing contact angle and surface coverage due to antireflection effects. For slightly absorbing droplets on the back with contact angles larger than the critical angle for total internal reflection at the droplet/air interface, the transmittance decreased by up to a factor 2 with increasing contact angle and surface area coverage. In the infrared spectral range when droplets were strongly absorbing, the window transmittance decreased by up to a factor 2.5 with increasing surface coverage for droplets either on the front or back sides. Experimental measurements were in excellent agreement with numerical predictions obtained using the Monte Carlo ray-tracing method. Then, the experimentally-validated simulation tool was used to predict the solar transmittance and emittance of glass windows covered with water droplets. The solar transmittance was found to decrease significantly with water droplets on either side depending on the time of day while the emittance remained unchanged.